Examining the innovative minds of Takaful consumers: the case of Malaysia - Hassan, Rusni; Kassim, Salina; Ab Rashid, Hafiz-Majdi; Salman, Syed Ahmed (R.K. Sharma, Institute of Medico-Legal Publications, 2018)
Objective: This study aims to examine the factors that will affect Malaysian consumers to participate in Takaful. Analysis: Out of the 600 questionnaires that were sent to consumers in greater Malaysia i.e. Kuala Lumpur and Selangor, we received 503 questionnaires. The sample is randomly selected from the known population. The total of 35 questions are constructed to know the determinants to choose new products by the respondents. Method: New product adoption theory is used in developing the questionnaire. In this, questions are organised into seven groups, namely, (a) cost vs. benefit, (b) accessability, availability and service quality, (c) product features, (d) reputation of the company, (e) attributes of agent, (f) marketing and promotion and (g) social and religious factors. The data collected from respondents were subjected to exploratory factor analysis based on Principal Component Analysis (PCA) through varimax rotation. This was performed in order to reduce the data to a manageable size. Findings: The findings show that, three predictors out seven predictors significantly contributed to the model and these are social and religious factors, product features, and marketing and promotion. Result: It can be said that, marketing, social and religion and product features are the most important and dominant factors that can influence Malaysian consumers to adopt and participate in Takaful products. Takaful operators should enhance their marketing strategy and simplify the product features to capture the untouched market.